Sparse seagrass meadows are critical dugong habitat: A novel rapid assessment of habitat-wildlife associations using paired drone and in-water surveys - Nicole E. Said; Christophe Cleguer; Paul Lavery; Amanda J. Hodgson; Connor Gorham; Julian A. Tyne; Ankje Frouws; Simone Strydom; Johnny Lo; Holly C. Raudino; Kelly Waples; Kathryn McMahon (Ecological Indicators)
Understanding the fine-scale behavioural and feeding ecology of marine megafauna is imperative for effective management of their habitat areas; however, obtaining the relevant data can be both costly and challenging. Here we integrate the use of small drones for dugong surveys with underwater benthic habitat assessment techniques at the local spatial scale (∼30 km2), to determine the drivers of dugong (Dugong dugon) distribution across three locations in the Pilbara, Western Australia. Paired assessment data was collected three times over two years. Benthic habitat (percent cover), seagrass nutritional quality and environmental parameters (temperature, water clarity, water current, water depth) were tested as predictor variables using generalised linear models, to examine drivers of both dugong presence/absence and abundance. We found that low cover (typical for this region; 2–10 %) of colonising seagrass is a key driver of the presence and abundance of dugongs. Halophila ovalis and Halodule uninervis were the main predictors of dugong presence and abundance across the three locations surveyed. Where both seagrass species simultaneously occurred, the likelihood of dugongs being present increased by over 60 times. The presence of H. uninervis alone was predicted to increase the abundance of dugongs by 1.4 times across all locations and by 6.8 times in one location, Exmouth Gulf, compared to when no seagrass was present. This study provided evidence of critical seagrass habitat, which is important knowledge for the protection and conservation of dugongs and their foraging habitat. The methods developed in this study could be employed in environmental impact assessments to predict and confirm potential seagrass forage habitat.